Electron transfer across anodic films formed on tin in carbonate-bicarbonate buffer solution - Gervasi, Claudio (2005)
Impedance and steady-state data were recorded in order to study the kinetics of electron transfer between passive tin electrodes and an electrolytic solution containing the K3Fe(CN)6-K 4Fe(CN)6 redox couple. Film thickness plays a key role in determining the type of electronic conduction of these oxide covered electrodes. Electron exchange with the oxide takes place with participation of the conduction band in the semiconducting film. A mechanism involving direct electron tunneling through the space charge barrier is the most suitable to interpret the experimental evidence. © 2004 Elsevier Ltd. All rights reserved.